Idealisation and stigmatisation of parenting in families with parental mental illness - Scott Yates; Lina Gatsou (Elsevier, 2021)
There has been growing recognition of the impacts of stigma for families where a family member has a mental illness, with findings suggesting families experience prejudice, discrimination and courtesy stigma, that judgments of blame for the development of the illness are applied especially to parent with unwell children, and that isolation and concealment of the illness is a common response. There is however relatively little work exploring presentation and manifestations of stigma specifically in families where a parent has a mental illness.In this paper we respond to calls for a broader consideration on stigma potentially spanning multiple domains of life by applying such a focus to exploring stigma in families where a parent has a mental illness. We present the results of reflexive thematic analysis of in-depth qualitative interviews and focus groups with families in the UK and multi-agency professionals who work with them to explore stigma is relation to the whole family.Our findings suggest that mental health stigma directed at and internalised by the ill parent is only one element of a complex set of manifestations of stigmatisation for families with a parent with mental illness. The majority of manifestations of stigma in our study are rooted not directly in mental health stigma, but in reflections on specific examples where a parent is perceived to have failed to perform a desired and normative parental role, even in relation to factors orthogonal to mental illness and its symptoms. This is directed at the unwell parent by other members of the family and is also the source of ruminative self-criticism by the ill parent themselves. The implications of these findings for conceptualising stigma in the broad context of families lives and social sources of parental normativity and stigma are explored.